A developmentally regulated cysteine proteinase in Dictyostelium discoideum. - Williams, J G (1985)
We have determined the sequence of a Dictyostelium mRNA encoding a protein with a high degree of homology to plant and animal cysteine proteinases. The degree of homology is highest in the region of the cysteine residue which is transiently acylated during peptide hydrolysis but all other residues known to be important in catalysis are also conserved. We have named this protein cysteine proteinase 1. There is a hydrophobic signal peptide of 18 amino acids and an additional 99 amino acids at the N terminus, which are not present in other cysteine proteases and which may be cleaved off during processing of the enzyme. There is a single copy of the gene in the Dictyostelium genome. The cysteine proteinase 1 mRNA is absent from growing cells and from cells isolated during the first 6 h of development but it constitutes approximately 1% of cellular mRNA by 10-12 h of development. During the development of Dictyostelium a major fraction of cellular protein is degraded to provide amino acids and a source of energy. Cysteine proteinase 1 may play a role in this auto-digestion.